Explaining levels of between-group and within-group inequality and poverty in South Africa - Priviledge Cheteni (Cogent Economics & Finance, 2019)
Most research on poverty has focused on causes of poverty and the inequality gap nationally, meanwhile increasing levels of inequality and poverty has actual occurred within population groups. This study focuses on the sources and extent of within-groups (intragroup; blacks African against each other) and between-groups (intergroup; whites, Indians, coloured and black Africans) inequality and poverty which varies more widely today than over the past decade. To achieve this, two harmonised General Household Surveys from 2012 and 2017 were utilised. The study found that poverty was mainly within-groups, yet, inequality was between-groups. Thus, more efforts should be directed in reducing poverty amongst black Africans within sub groups or tribal lines. Furthermore, income sources from agriculture and pension were the more elastic income components, suggesting that any changes in these two has the likelihood of worsening or reducing inequality. The study recommends that the government should focus on ways of boosting agricultural employment and social grants distribution.
Keywords: 330; FGT index; elasticities; inequalities; poverty; remittances